Penerapan Metode Eksperimen Berbantu Puzzle Picture Untuk Meningkatkan Hasil Belajar Siswa Materi Organ Pernapasan Manusia - Masrokhah Masrokhah (WASIS : Jurnal Ilmiah Pendidikan, 2021)
This study aims to describe the application of the puzzle picture-assisted experimental method to improve the learning outcomes of the human breathing apparatus for grade 5A students at SD Negeri Bintoro 5 in semester 1 of the 2019/2020 academic year.This research is a Classroom Action Research (CAR) consisting of 2 cycles, each cycle through stages, namely: planning, implementing, observing, and reflecting. The subjects of this study were students of class 5A SD Negeri Bintoro 5 Demak, totaling 38 students. Data collection techniques using test and observation techniques. The instruments used in data collection were in the form of evaluation test questions at the end of the cycle and observation sheets. Data analysis used quantitative and qualitative descriptive.The results of the study showed that there was an increase in learning outcomes for human respiratory equipment through the application of the experimental method assisted by the puzzle picture media in 5A grade students of SD Negeri Bintoro 5 in the 2019/2020 school year. The increase in the average value of student learning outcomes from the pre-cycle of 58 to 69 in the first cycle and increased to 80 in the second cycle. The percentage of students' completeness also increased from 10 students (26%) in the pre-cycle to 22 students (66%) in the first cycle and 36 students (95%) in the second cycle.